2021
DOI: 10.1096/fba.2021-00066
|View full text |Cite
|
Sign up to set email alerts
|

Neural regulations of the tumor microenvironment

Abstract: The identification of nerves in the tumor microenvironment has ushered in a new area of research in cancer biology. Numerous studies demonstrate the presence of various types of peripheral nerves (sympathetic, parasympathetic, sensory) within the tumor microenvironment; moreover, an increased density of nerves in the tumor microenvironment correlates with worse prognosis. In this review, we address the current understanding of nerve-mediated alterations of the tumor microenvironment and how they impact disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…Neurogenesis, similar to angiogenesis, is also an important modulator of cancer cells progression [ 87 ]. Literature data demonstrate the presence of nerves in the tumor microenvironment and their promotion of tumorigenesis and disease progression [ 88 ]. GO molecular function analysis revealed that among the discovered DEGs were those involved in kinase activity and protein binding.…”
Section: Discussionmentioning
confidence: 99%
“…Neurogenesis, similar to angiogenesis, is also an important modulator of cancer cells progression [ 87 ]. Literature data demonstrate the presence of nerves in the tumor microenvironment and their promotion of tumorigenesis and disease progression [ 88 ]. GO molecular function analysis revealed that among the discovered DEGs were those involved in kinase activity and protein binding.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions with the peripheral nervous system have been described in many tumors, including pancreatic, colorectal, and head and neck cancers, wherein sympathetic, parasympathetic, or sensory innervation influences tumor proliferation and invasiveness. 80 The unique characteristics of both glioma cells and the native cells of the CNS facilitate even more complex means of interaction ( Figure 2 ). Accumulating evidence suggests that bidirectional communication between the native nervous system cells and glioma cells can alter tumor growth kinetics and behavior.…”
Section: Nervous System Componentmentioning
confidence: 99%
“…Therefore, the VN is a critical neuronal communication channel between the CNS and the gut microbiota and is engaged in the bidirectional connection between the gut microbiota and brain [ 136 ]. Multiple types of peripheral nerves in the tumor microenvironment have been shown to influence cancer cell behavior [ 137 ], and the vagus nerve has anti-inflammatory properties mediated through ACh and 7nAChR that have been suggested to slow tumor progression [ 138 , 139 , 140 ]. Consequently, we believe that altering VN function by changing the flora may be a promising strategy for the future treatment of glioma.…”
Section: Impact Of the Local Environmentmentioning
confidence: 99%